ROCK2, but not ROCK1 interacts with phosphorylated STAT3 and co-occupies TH17/TFH gene promoters in TH17-activated human T cells. Issue 1 (December 2018) - Chen, Wei; Nyuydzefe, Melanie; Weiss, Jonathan; Zhang, Jingya; Waksal, Samuel; Zanin-Zhorov, Alexandra
Abstract Rho-associated coiled-coil kinase (ROCK)2 targeting down-regulates autoimmune responses in animal models and patients, however the underlying molecular mechanism is still an enigma. We report that ROCK2 binds phosphorylated-STAT3 and its kinase activity controls the formation of ROCK2/STAT3/JAK2 complex and optimal STAT3 phosphorylation in human CD4+ T cells during T helper 17 (TH17)-skewing. Moreover, chromatin-immunoprecipitation sequencing (ChIP-seq) analysis revealed that, genome-wide, about 70% of ROCK2 and STAT3 peaks overlapped and co-localized to several key genes controlling TH17 and T follicular helper (TFH) cell functions. Specifically, the co-occupancy of ROCK2 and STAT3 on theIrf4 andBcl6 genes was validated by ChIP-qPCR analysis. Furthermore, the binding of ROCK2 to both theIrf4 andBcl6 promoters was attenuated by STAT3 silencing as well as by selective ROCK2 inhibitor. Thus, the present study demonstrated previously unidentified evidence that ROCK2-mediated signaling in the cytosol provides a positive feed-forward signal for nuclear ROCK2 to be recruited to the chromatin by STAT3 and potentially regulates TH17/TFH gene transcription.